The impact of delayed instructional support on adult learners in the ODL context - Nantha Kumar , Subramaniam; Maheswari, Kandasamy (2012)
This paper investigated whether productive failure (PF) as an instructional strategy boosts students’ understanding on the subject matter in a face-to-face tutorial. PF instructional design advocates the delaying of support for the learners during the learning. This paper reports an initial study of a quasi-experimental that compares a ‘‘productive failure’’ instructional design with a traditional ‘‘lecture and practice’’ instructional design for a 2-hour tutorial session attended by adult learners. A total of 17 adult learners participated in the study. Learners experienced either a traditional lecture and practice teaching cycle or a PF cycle, where they solved complex problems in small groups without the provision of any support or scaffolds up until a consolidation lecture by their teacher during the last hour of the tutorial. Findings suggest that learners from the PF condition produced a variety of problem models and methods for solving the problems but were unsuccessful in their efforts, be it in groups or individually. Despite failing in their group and individual problem-solving efforts, learners from the PF condition performed better than their counterparts from the lecture and practice condition on both knowledge and higher order application problems based on the post-test. (Abstract by authors)